Knowledge, Attitudes, and Behavior Towards Salt Intake and Association With 24-hour Urinary Sodium Excretion in an Adult Population Cohort in Uruguay. (7th June 2021) - Moliterno, Paula; Donangelo, Carmen Marino; Borgarello, Luciana; Olascoaga, Alicia; Boggia, José
Abstract: Objectives: To examine the association between knowledge, attitudes and behavior towards salt use and its consumption estimated by urinary sodium excretion in a population adult cohort from Uruguay (Genotype Phenotype and Environment of Hypertension Study - GEFA-HT-UY). Methods: Participants [ n = 243; age 18–89y (min-max); 61.9% women], provided a single 24-hour urine sample validated according to volume and creatinine excretion. A questionnaire describing knowledge, attitudes and behaviors (KAB) was adapted from the WHO/PAHO protocol for population level sodium determination where participants answered on a range of scales. Anthropometric and blood pressure measurements were also taken. Associations between KAB categories and estimated salt intake were examined by general linear models, adjusted for sex, age tertiles and body mass index (BMI) categories. Results: Considering all participants, 35.8% were hypertensive (77% on antihypertensive treatment). Systolic/diastolic blood pressure was 125.6 ± 23.4/79.7 ± 9.9 mmHg, with no difference between sexes. Estimated salt intake was 7.8 ± 3.6 g (3116 ± 1433 mg sodium), higher in men (8.9 ± 3.9 g) compared to women (7.3 ± 3.3 g) ( P = 0.0013). Salt intake decreased with age tertiles ( P = 0.0001), and increased with BMI categories ( P = 0.0067). The majority (88.5%) of participants acknowledge that a high salt diet may cause serious health problems, 92.2% were unaware of WHO salt intake recommendation (<5 g/d) and 78.6% had intake over that limit. Only 12.4% considered they consumed "too much salt". Although 74.7% reported that limiting salt intake was important for their health, only 56% reported taking regular actions to control its intake. No difference in salt intake was found between participants who considered they use salt "too much" (8.5 ± 0.62 g), "the right amount" (7.9 ± 0.28 g), or "too little" (7.6 ± 0.52 g) ( P = 0.56). However, those who reported following a healthy diet had 1.4g lower salt intake than those who reported not doing so ( P = 0.016). There was no difference in salt intake between those who reported using/not using salt when cooking ( P = 0.65), and adding/not adding salt to food at table ( P = 0.087). Conclusions: No associations were found between knowledge, attitudes and behaviors towards salt use and intake. Perceived salt consumption underestimated salt intake. Funding Sources: CSIC, ANII, Uruguay.